Peran Masyarakat Lokal dalam Pelestarian Wisata Pohon Sejuta Umat di Kecamatan Kepulauan Banda - Merti Siska Rosely; Santri A.Wagola (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
This community service program aimed to explore and strengthen the role of local communities in preserving the natural tourism site known as "Pohon Sejuta Umat" in Banda District, Central Maluku. This site holds ecological, cultural, and spiritual value, making community involvement vital for its sustainability. The program employed participatory methods including observations, interviews, focus group discussions, and training workshops with community members, traditional leaders, and the local tourism awareness group (Pokdarwis). The findings reveal strong community commitment in conserving the area through regular clean-ups, informational signage based on local wisdom, and collaborative patrols. Capacity-building sessions enhanced community understanding of environmental conservation and introduced digital strategies to promote the site. This initiative underscores the importance of integrating local knowledge and participatory approaches in sustainable tourism development. Empowering local communities ensures that conservation efforts align with both environmental goals and socio-economic benefits.